Malaria-Infected Mice Are Cured by a Single Low Dose of a New Silylamide Trioxane Plus Mefloquine - Theresa A. Shapiro; Gary H. Posner; Nirbhay Kumar; Bryan T. Mott; Vandana Singhal; Lauren E. Woodard (MDPI AG, 2009)
Three thermally and hydrolytically stable silylamide trioxanes have been prepared from the natural trioxane artemisinin in only five simple chemical steps and in at least 56% overall yield. Two of these new chemical entities completely cured malariainfected mice at a single oral dose of only 8 mg/kg combined with 24 mg/kg of mefloquine hydrochloride. The high efficacy of this ACT chemotherapy is considerably better than the efficacy using the popular trioxane drug artemether plus mefloquine hydrochloride.